Hubungan parental attachment dengan kecerdasan emosi pada remaja awal - Fara Pradika Putri; Sofa Amalia; Retno Firdiyanti (Cognicia, 2022)
Cases of violence in early adolescent still often occur due to lack of emotional regulation. One of the factors behind adolescent emotional intelligence is parental attachment. This study aims to determine the relationship between father attachment and emotional intelligence in early adolescence and the relationship between mother attachment and emotional intelligence in early adolescence. The research design is correlational quantitative research with sampling using non-probability voluntary sampling technique. The subjects in this study were 237 early adolescents aged 12-15 years and had both parents. The scale used in this study is an attachment scale using the Inventory of Parent and Peer Attachment Revised Version (IPPA-R) and an emotional intelligence scale using a scale based on Goleman's theory. Pearson's correlation analysis showed that there was a relationship between attachment of father (r = 0.288; p < 0.05) and mother (r = 0.415; p < 0.05) with emotional intelligence in early adolescence. Keywords: attachment mother and father, emotional intelligence, early adolescence